1986
DOI: 10.3109/00016358608997720
|View full text |Cite
|
Sign up to set email alerts
|

Dental maturity in Finnish children, estimated from the development of seven permanent mandibular teeth

Abstract: Overall dental maturity was studied semilongitudinally in a group of 248 healthy children born in Helsinki in 1968-73. In all, 738 orthopantomograms were taken of these children at ages of 2.5-16.5 years. Overall dental maturity was estimated by the method of Demirjian and Goldstein, which is based on the development of seven left mandibular permanent teeth. The aim of the study was to construct dental maturity curves for Finnish children and to compare their dental maturity with that of French-Canadian childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
60
1
3

Year Published

1993
1993
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(80 citation statements)
references
References 8 publications
12
60
1
3
Order By: Relevance
“…Previously, several studies investigated the suitability of the Demirjian method in populations that differed from Canadians (1,(6)(7)(8)10,(12)(13)(14)(15)(16)22,24,25). All of these studies have demonstrated that the Demirjian method overestimated age between 0.04 years (12) to 3.04 years (1).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, several studies investigated the suitability of the Demirjian method in populations that differed from Canadians (1,(6)(7)(8)10,(12)(13)(14)(15)(16)22,24,25). All of these studies have demonstrated that the Demirjian method overestimated age between 0.04 years (12) to 3.04 years (1).…”
Section: Discussionmentioning
confidence: 99%
“…While stages of tooth mineralization in dry bones are directly comparable to radiographic standards from living samples, living population standards for tooth emergence through the gingiva are not the same as observations of tooth emergence through the alveolus on dry bones (Demirjian, 1986;Merchant, 1973;Trodden, 1982). In addition, only a few published studies are suitable for use in age prediction because they include data for a number of teeth, consist of large reference samples and have an applicable methodology for reporting ages (Anderson et al, 1976;Demirjian et al, 1973;Demirjian and Goldstein, 1976;Haavikko, 1970;Kataja et al, 1989;Moorrees et al, 1963a,b;Nystrom et al, 1986). Other studies that use maturity scales (Demirjian et al, 1973;Demirjian and Goldstein, 1976) in reporting tooth formation chronologies are difficult for osteological researchers to apply.…”
mentioning
confidence: 99%
“…By scoring the seven mandibular teeth to assess dental age, local disturbing factors of the oral cleft or a surgical trauma, could be excluded. However, the original scores for French-Canadian children could not be used for comparison with Dutch children, since the rate of maturation may be influenced by both heredity and environment (Jordan et al, 1966;Pelsmakers et al, 1997), and maturity standards may change from one population to another (Loevy, 1983;Nyström et al, 1986;Pöyry et al, 1989). Therefore, a control group of Dutch children without oral clefts was also investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, statistically significant differences were found for the place of birth (Pöyry et al, 1989) and for the population investigated (Nyström^a/., 1986;Loevy, 1983).…”
Section: Introductionmentioning
confidence: 98%